Mesoporous supraparticles with a tailored solid-liquid-gas interface for visual indication of H2 gas and NH3 vapours - Zink, Andreas; Reichstein, Jakob; Ruhland, Nico; Stockinger, Nina; Morozov, Boris; Cuadrado Collados, Carlos; Thommes, Matthias; Kataev, Evgeny; Wintzheimer, Susanne; Mandel, Karl (Chemical Communications, 2024)
Dual-gasochromic supraparticles that undergo rapid eye-readable and gas-specific colour changes upon reaction with hydrogen or ammonia are reported. This functionality is achieved by tailoring the solid-liquid-gas interface within the mesoporous framework of supraparticles via spray-drying.
CRIS-Team Scopus Importer:2024-06-14